Communication and its impact on enterprise financial sustainability - Kapepula, Annie (Research of GSB, 2018)
This study investigates the impact of value communication on financial sustainability of not for profits set up as small to medium scale enterprises. The major objective is to determine whether there is a significant impact on the financial sustainability if not for profits create a more aggressive approach and innovate way of communicating with financiers and donors on matters concerning their strategic plans and budgets. The four pillars of financial sustainability have been considered focusing mostly on Strategic and financial planning or budgeting. Measuring sustainability for a not for profit differs from that of a profit making enterprise in that measures such as return on capital employed would be meaningless since most not for profit have a low capital base and are not bottom-line focused. The independent variable has been identified as value communication of strategic and financial planning or budgeting with donors or potential funders while the dependent variable is financial sustainability defined as meeting current budgetary demands. Moderating and Intervening variables identified include ; global financial environment ,operating environment, policy position of donor funding states, donor funding policies, goals and objectives, structure of donor funding towards development programmes and projects and CEO charisma and communication attributes. The study followed a survey design, and employed Times Series as evaluative method for quantitative analysis. Analysis was based on primary data generated through a structured questionnaire administered on respondents. Respondents were employees in selected not for profit organizations working in the four key development services supporting the Millennium Development Goals and Sixth National Development Plan, namely Health, Education, Agriculture and Water and Sanitation in Zambia. Interviews were also conducted with various financiers and donors of the selected not for profit enterprises. Responses to research statements were scaled and converted to quantitative data via Likert scale developed for the study to enable segmentation of the data responses into dependent and independent variables based on communication and financial sustainability variables. This study will help not for profits create an innovative communication strategy so as not to risk losing funding to other competitors or new comers on the scene.